Likely role of APOBEC3G-mediated G-to-A mutations in HIV-1 evolution and drug resistance. - Patric Jern; Rebecca A Russell; Vinay K Pathak; John M Coffin (PLoS Pathogens, 2009)
The role of APOBEC3 (A3) protein family members in inhibiting retrovirus infection and mobile element retrotransposition is well established. However, the evolutionary effects these restriction factors may have had on active retroviruses such as HIV-1 are less well understood. An HIV-1 variant that has been highly G-to-A mutated is unlikely to be transmitted due to accumulation of deleterious mutations. However, G-to-A mutated hA3G target sequences within which the mutations are the least deleterious are more likely to survive selection pressure. Thus, among hA3G targets in HIV-1, the ratio of nonsynonymous to synonymous changes will increase with virus generations, leaving a footprint of past activity. To study such footprints in HIV-1 evolution, we developed an in silico model based on calculated hA3G target probabilities derived from G-to-A mutation sequence contexts in the literature. We simulated G-to-A changes iteratively in independent sequential HIV-1 infections until a stop codon was introduced into any gene. In addition to our simulation results, we observed higher ratios of nonsynonymous to synonymous mutation at hA3G targets in extant HIV-1 genomes than in their putative ancestral genomes, compared to random controls, implying that moderate levels of A3G-mediated G-to-A mutation have been a factor in HIV-1 evolution. Results from in vitro passaging experiments of HIV-1 modified to be highly susceptible to hA3G mutagenesis verified our simulation accuracy. We also used our simulation to examine the possible role of A3G-induced mutations in the origin of drug resistance. We found that hA3G activity could have been responsible for only a small increase in mutations at known drug resistance sites and propose that concerns for increased resistance to other antiviral drugs should not prevent Vif from being considered a suitable target for development of new drugs.